An HTS 21-pole microstrip filter for IMT-2000 base stations with steep attenuation. - Hattori, W.
We developed a 21-pole high-temperature superconductor thin-film microstrip filter with steep attenuation. This filter is applicable in the International Mobile Telecommunications-2000 (IMT-2000) base station receiver system, where high selectivity is needed to avoid interference from signals in the personal handyphone system (PHS) band just below the IMT-2000 band. The out-of-band rejection of this filter 1 MHz below the passband edge is more than 40 dB. Owing to the improvements of the design and the fabrication processes, we also eliminated the need for a tuning process in the fabrication processes in order to reduce the production costs and the turnaround time.
Keywords: IMT-2000 base station receiver; Attenuation; Fabrication process; Multipole high temperature superconductor thin film microstrip filter